Optimising land transport resources : Improving fleet management using cost efficiency effectiveness - Noorhafizan, A.Talib (2024)
In the context of evolving geopolitical dynamics and budget constraints, optimizing land transport resources has become crucial for the Royal Malaysian Air Force (RMAF). This study explores strategies to enhance fleet management through cost efficiency effectiveness. The research investigates the application of emerging technologies such as telematics, artificial intelligence (AI), and the Internet of Things (IoT) to improve operational efficiency and reduce costs. It identifies key operational challenges, including inefficient vehicle allocation, limited real-time tracking capabilities, and reactive maintenance practices. Additionally, the study evaluates the current training programs for RMAF personnel to ensure they are equipped to manage modern fleet management systems effectively. By analysing both internal and external factors impacting fleet utilization, this research provides actionable insights for the RMAF to enhance its operational readiness and strategic capabilities while navigating financial constraints. The findings aim to support the development of a more agile, cost-effective fleet management system that aligns with the RMAF’s mission to maintain national security and contribute to regional stability.